THE EFFECTIVENESS OF DIGITAL MARKETING AND THE CONSISTENCY OF ISLAMIC BRANDING ON CUSTOMER INTEREST IN USING THE BSI MOBILE APPLICATION - Salsabila, Salsabila; Rahayu, Yayuk Sri (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2024)
This research aims to assess the impact of Digital Marketing and Islamic Branding on Customer Interest in using the BSI mobile application. Conducted on 100 BSI mobile customers, quantitative research using multiple linear regression and analysis using SPSS 26. Data was collected through questionnaires. The results show that Digital Marketing and Islamic Branding have a positive and significant effect on Customer Interest. The findings confirm that both play an important role in shaping customer interest, with Islamic Branding which includes BSI's positive image in implementing sharia principles, sharia-based products and halal labels providing an overall positive impact. Thus, it can be concluded that the influence of Digital Marketing and Islamic Branding on Customer Interest in using the BSI mobile application has proven to be significant.